Moral Perfection and the Demand for Human Enhancement - Warmbier, Adriana (ETHICS IN PROGRESS, 2015)
In this article I discuss one of the most significant areas of bioethical interest, which is the problem of moral enhancement. Since I claim that the crucial issue in the current debate on human bioenhancement is the problem of agency, I bring out and examine the conditions of possibility of selfunderstanding, acting subjects attributing responsible authorship for their actions to themselves. I shall argue that the very idea of moral enhancement, properly understood, fails to justify the claims that enhancing the “biological” factor that plays a part in the process of making moral choices, whether through biomedical or genetic interventions, will actually increase the probability of having “morally better future motives”.